2013
DOI: 10.1002/etc.2381
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salinity exposure on multiple life stages of a common freshwater mussel, Elliptio complanata

Abstract: There is growing concern over the effects of increased salinization on freshwater organisms, which are largely unknown for unionid mussels. Adult and larval Elliptio complanata were exposed to low-level salt concentrations to determine the effects on mussel survival, physiology, and reproduction. Adults were exposed to salt concentrations of 0 parts per thousand (ppt), 2 ppt, 4 ppt, and 6 ppt NaCl and monitored over 7 d for mortality. Treatment groups exposed to 6 ppt and 4 ppt experienced 50% mortality at day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Freshwater mussel sensitivity to major ions has been most studied in laboratory settings for NaCl solutions in reconstituted waters of varying hardness. Such studies have found acute toxicities for NaCl to vary widely among freshwater mussel species (Valenti, ; Bringolf et al ., ; Gillis, ), among life stages (Bringolf et al ., ; Blakeslee et al ., ), and with water hardness (Gillis, ). Gillis () also found acute toxicity to native mussel glochidia at lower NaCl concentrations in laboratory reconstituted waters than in natural river waters, suggesting that the full range of water chemistry is influential as demonstrated for laboratory test organisms by Mount et al .…”
Section: Collective Interpretationmentioning
confidence: 97%
“…Freshwater mussel sensitivity to major ions has been most studied in laboratory settings for NaCl solutions in reconstituted waters of varying hardness. Such studies have found acute toxicities for NaCl to vary widely among freshwater mussel species (Valenti, ; Bringolf et al ., ; Gillis, ), among life stages (Bringolf et al ., ; Blakeslee et al ., ), and with water hardness (Gillis, ). Gillis () also found acute toxicity to native mussel glochidia at lower NaCl concentrations in laboratory reconstituted waters than in natural river waters, suggesting that the full range of water chemistry is influential as demonstrated for laboratory test organisms by Mount et al .…”
Section: Collective Interpretationmentioning
confidence: 97%
“…To establish E. complanata as an experimental model for salt stress in freshwater ecosystems, we sought to establish the range of acute NaCl doses that are lethal , the physiological impacts of sublethal exposures of various durations , and whether transcriptional responses of genes implicated in the salt response in other species (e.g., NKA, Hsp70s, aquaporins, and the taurine synthesis pathway) are also expressed in a manner consistent with expectation (present study). These initial steps are important so that the subsequent prioritization of candidate biomarker genes has a sound biological footing.…”
Section: Discussionmentioning
confidence: 82%
“…Assembly and annotation of the transcriptome to support RNA‐Seq and other analyses are described in Cornman et al . Details of the collection of mussels, their housing and care in the laboratory, and salinity exposures are described briefly in the present study and more fully in Blakeslee et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic invertebrates regulate their ionic balance at an energetic cost (Bradley, 2008;Jonusaite et al, 2011), which can be translated into less energy available for other biological functions and reduced fitness. Although not many studies are available, there are evidences that elevated salinities can reduce egg hatchling (Kefford et al, 2004;Paradise, 2009), larval recruitment (Blakeslee et al, 2013) and growth Johnson et al, 2014), and increase time to emergence of larvae as flying adults (Hassell et al, 2006;Lob and Silver, 2012;Hale et al, 2014). One important sub-lethal effect that has yet to be investigated is changes in predation efficiency (i.e.…”
Section: Introductionmentioning
confidence: 98%